Pengukuran Indeks Masa Tubuh (IMT) untuk Penentuan Status Gizi Ibu Hamil di Posyandu Prima Desa Congkrang Kecamatan Muntilan Kabupaten Magelang - Eniyati Eniyati; Afi Lutfiyati; Ratna Prahesti; Reni Merta K (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
Body Mass Index (BMI) is used as an indicator of a pregnant woman’s nutritional status and as a basis for recommendations on weight gain during pregnancy. A mother’s nutritional status before and during pregnancy can affect the growth of the fetus she is carrying (Ministry of Health of the Republic of Indonesia, 2019). If a mother's nutritional status is poor, either before pregnancy or during pregnancy, or if her Body Mass Index (BMI) is low, it has a negative effect on pregnancy outcomes, usually resulting in low birth weight (LBW) or preterm birth. Measuring BMI is a simple way to monitor the nutritional status of adults, especially regarding underweight and overweight issues. BMI is calculated based on body weight in kilograms (kg) divided by height in meters squared (m²). BMI is not related to gender and applies to adults (>18 years). The normal BMI threshold for Indonesia is 18.5–25.0. Mothers with body weight below the minimum are classified as